The Arabidopsis Anaphase‐Promoting Complex/Cyclosome Subunit 1 is Critical for Both Female Gametogenesis and Embryogenesis1. Issue 1 (21st January 2013) - Wang, Yanbing; Hou, Yingnan; Gu, Hongya; Kang, Dingming; Chen, Zhang‐Liang; Liu, Jingjing; Qu, Li‐Jia
Abstract Anaphase‐promoting complex/cyclosome (APC/C), a multisubunit E3 ligase, plays a critical role in cell cycle control, but the functional characterization of each subunit has not yet been completed. To investigate the function of APC1 in Arabidopsis, we analyzed four mutant alleles of APC1, and found that mutation in APC1 resulted in significantly reduced plant fertility, accumulation of cyclin B, and disrupted auxin distribution in embryos. The three mutant alleles apc1–1, apc1–2 and apc1–3 shared variable defects in female gametogenesis including degradation, abnormal nuclear number, and disrupted polarity of nuclei in the embryo sac as well as in embryogenesis, in which embryos were arrested at multiple stages. All of these defects are similar to those previously identified in apc4. The mutant apc1–4, in which the T‐DNA was inserted after the transmembrane domain at the C‐terminus, showed much more severe phenotypes; that is, most of the ovules were arrested at the one‐nucleate female gametophyte stage (stage FG1). In the apc1 apc4 double mutants, the fertility was further reduced by one‐third in apc1–1/+ apc4–1/+, and in some cases no ovules even survived in siliques of apc1–4/+ apc4–1/+. Our data thus suggest that APC1, an essential component of APC/C, plays a synergistic role with APC4 both in female gametogenesis and in embryogenesis.